Simbol Perlawanan dalam Cerita Rakyat Arekan Jawa Timur: Perspektif Semioantropolitik - Dawudi, Dandy Ashghor; Ahmadi, Anas (Deiksis, 2024)
Folklore which is born and develops as collective memory is a product of a society's culture, through folklore the cultural character of a society can be recognized. This research aims to dissect the esoteric symbols contained in folklore in East Java arekan culture to determine the character of resistance contained in the story using Zizek's theory of the subject of rebellion. The folklore that the author will examine is the folklore of Sawunggaling, Sarip Tambak Oso, Joko Sambang. This research uses a qualitative descriptive method with an ethnographic folklore study approach. The results of this research found a common thread in East Javanese arekan folklore, namely the character of resistance which is egalitarian and the spirit of resistance which is not motivated by ideological, palace-centric and chauvis motifs, but is motivated by oppression due to injustice experienced by the people.